OCORRÊNCIA DE AEROMONAS SPP. EM ABATEDOURO BOVINO E SENSIBILIDADE A ANTIMICROBIANOS - Martineli, T.m. [UNESP]; Rossi, O.d [UNESP]; Cereser, N.d. [UNESP]; Cardozo, M.v. [UNESP]; Kamimura, B.a. [UNESP]; Nespolo, N.m. [UNESP]; Pinto, F.r. [UNESP] (Instituto Biológico, 2020)
The genus Aeromonas comprises important human pathogens, gastroenteritis being the most common type of infection attributed to these bacteria. Considering their importance as foodborne pathogens, the occurrence of Aeromonas spp. was studied on bovine carcasses and the environment of a slaughterhouse in São Paulo State, Brazil. A total of 285 samples were collected from 19 points. Direct counting was carried out by seeding on selective medium, with biochemical characterization of the species after selective enrichment and antimicrobial sensitivity testing. The direct count permitted bacteria quantification only in 12 samples ranging from 0.5 to 9.2 x 100 CFU/ cm2, of which 5 were from environment, ranging from 1.0 x 100 to 3.0 x 100 CFU/plate. However, after selective enrichment,Aeromonas spp. was isolated from 38 samples, which when added to the environmental samples not subjected to the enrichment provided 62 isolates for analysis. Biochemical characterization allowed for the verification of the occurrence of 59 isolates of A. caviae, 1 ofA. sobria, 1 ofA. trota and 1 ofA. schubertii. Antimicrobial testing revealed that all isolates were resistant to ampicillin and cephalotin, while the results for the other antimicrobials were variable. Resistance of all isolates to some antimicrobials indicates that these must be used carefully to avoid early development of multiresistantAeromonas spp. Also, the greatest prevalence of A. caviae must be considered relevant because it is one of the causative species of human gastroenteritis.

O gênero Aeromonas compreende espécies consideradas importantes patógenos para os seres humanos, sendo as gastroenterites as infecções mais comumente atribuídas a estas bactérias. Tendo em vista sua importância como patógeno de origem alimentar, a ocorrência deAeromonas spp. foi estudada em carcaças bovinas e ambiente do abatedouro em uma indústria do Estado de São Paulo. Foram colhidas 285 amostras de 19 locais. Foi realizada a contagem direta por semeadura em meio seletivo, caracterização bioquímica das espécies após enriquecimento seletivo e teste de sensibilidade a antimicrobianos. A contagem direta permitiu a quantificação dessas bactérias em apenas 12 amostras, variando de 0,5 a 9,2 x 100 UFC/cm2, sendo cinco delas de ambiente, com populações que variaram de 1,0 x 100 a 3,0 x 100 UFC/placa. Entretanto, após o enriquecimento seletivo, Aeromonas spp. foram isoladas de 38 amostras que, somadas às amostras de ambiente não submetidas ao enriquecimento, forneceram 62 isolados para análise. A caracterização bioquímica das espécies permitiu verificar a ocorrência de 59 isolados de A. caviae, um de A. sobria, um de A. trota e um de A. schubertii. O teste com antimicrobianos revelou resistência de todos os isolados pela ampicilina e cefalotina, enquanto, para os demais antimicrobianos, esta foi variável. A resistência da totalidade dos isolados a determinados antimicrobianos indica que estes devem ser utilizados criteriosamente com a finalidade de evitar o surgimento precoce de cepas deAeromonas spp. multirresistentes. Ainda, a maior prevalência deA. caviae deve ser considerada relevante, pois trata-se de uma das espécies causadoras de gastroenterite em humanos.
OCCURRENCE OF AEROMONAS SPP. IN BOVINE ABATTOIR AND ANTIMICROBIAL SENSITIVITY
Keywords: Aeromonas spp; antimicrobial sensitivity; bovine abattoir; Aeromonas spp; sensibilidade antimicrobiana; abatedouro bovino